Students Satisfaction toward the Learning Environment Management of Khlong Mai School under the Jurisdiction of Samut Prakan Primary Education Service Area Office 1 - Kumboonruang, Waraporn; Kohtbantau , Sunthon (Journal for Developing the Social and Community, 2022)
The research purposes were: (1) to study the students satisfaction level toward the learning environment management of Khlong Mai School under the jurisdiction of Samut Prakan Primary Education Service Area Office 1, and (2) to compare the students satisfaction toward the learning environment management of Khlong Mai School under the jurisdiction of Samut Prakan Primary Education Service Area Office 1, classified by gender and class level. The population was the students of Grade 4-6 (Primary school level 4-6) and Grade 7-9 (Secondary school level 1-3) of Khlong Mai School under the jurisdiction of Samut Prakan Primary Education Service Area Office 1. The sample group was the 210 teachers. The research instrument was the 5-levels estimate rating scale questionnaire with 60 items and reliability .86, selected by sample random sampling. The data analysis statistics were the percentage, mean, standard deviation, and t-test. The research findings were: 1. The student satisfaction toward the learning environment management found the overall was at high level. When each aspect consideration found all aspects were at high level; the highest mean was the organizing student activities aspect, followed by the friend social group aspect, and the least mean was the facilities and buildings aspect. 2. The student satisfaction toward the learning environment management found the students with different of gender and classroom level had the satisfaction toward the learning environment management did not different.